If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3c+5=6(c-3)
We move all terms to the left:
3c+5-(6(c-3))=0
We calculate terms in parentheses: -(6(c-3)), so:We get rid of parentheses
6(c-3)
We multiply parentheses
6c-18
Back to the equation:
-(6c-18)
3c-6c+18+5=0
We add all the numbers together, and all the variables
-3c+23=0
We move all terms containing c to the left, all other terms to the right
-3c=-23
c=-23/-3
c=7+2/3
| -3z+7=16 | | -6y-3=-2y+7-4y | | z-13=17 | | 18j-16j=-16 | | 1/5x+4=2/5x-3 | | 1/5x+4=25x-3 | | 17b=15 | | 7-4x=3x^2-10x+2 | | x/12-1/2=3/8 | | 4x²-90=10 | | 19t=12 | | -12n=192 | | 3=-11+v | | 12x²-18x+6=0 | | 1=4k+2 | | -11/2=19/6y-7/3 | | y/2+8=3y-2 | | 6v=102 | | 58-10k=3k+6 | | 5x^2-6x=-38 | | 2(x-2)=2x–4 | | 2p^2+9=15 | | (11x-15)=5x-13 | | -r+16=-20+5r | | 3.6w=2(.8w+12) | | 0.1(x+50)=−3x−13+4x | | 2(5x+2)=-2(5x-5)-3x | | 6x^2-8x+1=x+4 | | 2(3x+1)=7(2+x) | | )-3(x-5))/5=(3(-2x+1))/4 | | 58-10k=3k-6 | | P(x)=X^3-x-5 |